Kinematics differences between one-handed and two-handed tennis backhand using gyroscopes. An exploratory study - Ruiz-Malagón, E. J.; Delgado-García, G.; Ritacco-Real, M.; Soto-Hermoso, V. M. (International Journal of Racket Sports Science, 2022)
The main objective of this article is to compare angular kinematics and intersegmental coordination of the upper limbs between one-handed and two handed backhands in a sample of 20 male competition players by using gyroscopes and compare ball speeds and accuracy obtained in both types of backhands. The angular kinematics, intersegmental coordination, ball speed and accuracy were compared during a specific stroke performance test using four inertial sensors (trunk, head, arm and forearm). We hypothesize that there will be significant differences in terms of ?peak and intersegmental coordination in some of the segments measured between DH and SH by using gyroscopes, but the opposite will happen in the variables speed ball and accuracy. There are no significant differences between one-handed backhand and two-handed backhand in terms of speed and accuracy. Higher peaks angular speeds were found in the trunk and arm over the x axis in two-handed backhand which could indicate that this type of backhand generates greater trunk rotation and external rotation of the arm and forearm compared to one-handed backhand. The peak angular speeds were greater in the arm and forearm on the z axis in the case of one-handed backhand which is related to a greater extension of the forearm accompanied by a higher termination in the technical gesture. In conclusion, the proposed model of biomechanical analysis through the use of gyroscopes is especially useful for kinematic analysis of tennis strokes during field-based experimentation and could easily be adapted to other sports. It is also a low-cost and portable alternative that includes all instrumentation and data processing.